2014
DOI: 10.1017/s0022109014000489
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Free Measure of Aggregate Idiosyncratic Volatility and the Prediction of Market Returns

Abstract: In this paper, we formally show that the cross-sectional variance of stock returns is a consistent and asymptotically efficient estimator for aggregate idiosyncratic volatility. This measure has two key advantages: It is model free and observable at any frequency. Previous approaches have used monthly model-based measures constructed from time series of daily returns. The newly proposed cross-sectional volatility measure is a strong predictor for future returns on the aggregate stock market at the daily freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 53 publications
0
32
0
1
Order By: Relevance
“…Similar to Bakaert et al 2012, Nartea et al (2013) and Garcia et al (2014), we fit the Markov regimeswitching model with a first-order autocorrelation structure (AR (1)) for three volatility components, and particularly interested in the idiosyncratic volatility. In this model, two regimes are indexed by a discrete state variable ( ), following a Markov-chain process with constant transition probabilities.…”
Section: Regimes Switchingmentioning
confidence: 99%
“…Similar to Bakaert et al 2012, Nartea et al (2013) and Garcia et al (2014), we fit the Markov regimeswitching model with a first-order autocorrelation structure (AR (1)) for three volatility components, and particularly interested in the idiosyncratic volatility. In this model, two regimes are indexed by a discrete state variable ( ), following a Markov-chain process with constant transition probabilities.…”
Section: Regimes Switchingmentioning
confidence: 99%
“…Meanwhile, another strand of the literature provides ample evidence linking stock market volatility to real economic activity [4,5] and stock market volatility to future aggregate stock returns [27][28][29][30]. In a recent study, applying linear and nonlinear causality tests, Choudhry et al [6] showed that a bidirectional causal relationship exists between stock market volatility and the business cycle in a sample of four major economies without using return dispersion in their multivariate tests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Para este estudo, a CSV foi desenvolvida usando como base Garcia et al (2014). Considerando a CSV ponderada em igualdade, a seguir denominada CSV t EW em que w it = 1/N t i e t. Assumindo que r t EW representa o retorno do portfólio igualmente ponderado, tem-se:…”
Section: Amostraunclassified